Endoscopic Ultrasonographic Findings of Pancreatic Parenchyma and Ductal System in Patient with Chronic Pancreatitis - Kafle, Roshan; Shrestha, Ramila; Paudel, Mukesh Sharma; Khanal, Ajit; Khadka, Dibas (Nepal Medical College Journal, 2025)
Chronic pancreatitis is a progressive inflammatory disorder characterized by irreversible morphological changes in the pancreas, leading to persistent abdominal pain, malabsorption, and diabetes mellitus due to endocrine and exocrine insufficiency. A total of 53 patients diagnosed with chronic pancreatitis were evaluated using endoscopic ultrasonography (EUS) at Bir Hospital focusing on both pancreatic parenchymal and ductal changes. Biliary abnormalities were also recorded. EUS revealed that increased parenchymal echogenicity was the most common finding, present in 69.8% of cases. Pancreatic atrophy was observed in 20.8%, while intra-parenchymal calcifications appeared in 30.2% of patients. Cystic collections were found in 24.5%, and hyperechoic strands without shadowing were noted in 35.8%. Hyperechoic foci without shadowing were seen in 5.7% of cases. Ductal findings were also prominent, with a dilated main pancreatic duct (MPD) in 58.5% of patients and intraductal stones present in 34.0%. Irregular MPD contours were noted in 15.1%, while dilated side branches were less common, found in only 1.9%. Additionally, biliary involvement was observed in a subset of patients, with dilated common bile duct (CBD) and CBD stones both present in 7.5% of cases, and distal CBD narrowing in 17.0%. EUS is an effective tool for evaluation of pancreatic parenchymal and ductal changes in chronic pancreatitis.